Visionary observers : anthropological inquiry and education - Cherneff, Jill B. R.; Hochwald, Eve (Critical studies in the history of anthropology., 2006)
Explores the relationship between anthropology and public policy, examining nine twentieth-century American anthropologists who made important contributions to debates about race, ethnicity, socialization, and education. The topics they addressed illustrate how the lens of American anthropology has long been focused on domestic issues.